Effect of low-intensity ultrasound on partial nitrification: Performance, sludge characteristics, and properties of extracellular polymeric substances - Shuai Tian; Shuchang Huang; Yichun Zhu; Guangming Zhang; Junfeng Lian; Zuwen Liu; Linan Zhang; Xinxin Qin (Ultrasonics Sonochemistry, 2021)
Ultrasound technology, which is environment-friendly and economical, has emerged as a novel strategy that can be used to enhance the partial nitrification process. However, its effect on this process remains unclear. Therefore, in this study, partial nitrification sludge was subjected to low-intensity (0.15 W/mL) ultrasound treatment for 10 min, and the effect of ultrasonic treatment on the partial nitrification process was evaluated based on changes in reactor performance, sludge characteristics, and the properties of extracellular polymeric substances (EPS). The results obtained showed that the ultrasonic treatment enhanced nitrite accumulation performance as well as the activity of ammonia-oxidizing bacteria from 3.3 to 16.6 mg O2/g VSS,⋅while inhibiting the activity of nitrite-oxidizing bacteria. Further analysis showed that owing to the ultrasonic treatment, there was an increase in EPS contents. Particularly, there was a significant increase in loosely bound polysaccharide (PS) contents, indicating the occurrence of intracellular PS anabolics as well as PS secretion. Additionally, ultrasonic treatment induced a significant increase in carbonyl, hydroxyl, and amine functional group contents, and EPS analysis results revealed that it had a positive effect on mass transfer efficiency; thus, it enhanced the partial nitrification process. Overall, this study describes the effect of intermittent low-intensity ultrasound on the partial nitrification process as well as the associated enhancement mechanism.